GE_GERICHTE P/11034/2024 vom 23. Mai 2025 - GE Cour de justice (2025)
DÉFENSE DE CHOIX;DROIT D'ÊTRE ENTENDU;INDEMNITÉ(EN GÉNÉRAL);ORDONNANCE DE NON-ENTRÉE EN MATIÈRE | CPP.429.al1.leta; CPP.429.al2; CPP.429.al3; Cst.29.al2